A Patient With Dysphagia due to an Aortic Aneurysm - Kim, Jeong-Ho; Jang, Sung-Won; Kim, Dong-Bin; Lee, Hyun-Jeong; Kim, Jae-Gyung; Kwon, Bum-Jun; Cho, Eun-Ju; Rho, Tai-Ho; Kim, Jae-Hyung (Korean circulation journal, 2009)
Dysphagia aortica is difficulty in swallowing caused by extrinsic compression of the esophagus due to an ectatic, tortuous, or aneurysmatic atherosclerotic thoracic aorta. This condition is very uncommon, and it is usually associated with old age, women with short stature, hypertension, and kyphosis. We report herein a case involving a patient with dysphagia who had an aortic aneurysm.